Strength for each day [large type] : 365 devotions to make every day a great day - Meyer, Joyce, 1943- (FaithWords, 2021)
Discover a powerful and positive mindset each day of the year with uplifting insights and motivational Bible verses provided by #1 New York Times bestselling author Joyce Meyer. Find new mercies and blessings each day when you spend time with God: reading His Word, listening, and praying for His direction. When you do, God will strengthen and enable you to handle life peacefully and wisely instead of merely trying to get through the day. He will renew your strength and empower you to bear up under trials with patience, so you can experience them with a good attitude. Maintaining a positive view in the midst of something unpleasant is the key to victory, and it enables you to enjoy the journey! With the constant demands and pressures of daily life, it can be hard to regularly pause to be with and listen to God's voice. Joyce's practical teaching format in this 365-day devotional will encourage you to take the time for yourself so that you can receive Strength for Each Day!